ANALISIS IMPLEMENTASI UNIT PENANGGULANGAN KEADAAN DARURAT KEBAKARAN DI MALL X, JAKARTA - Rosiana Agustin; Bina Kurniawan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The limitation of green space at big city like Jakarta make people have no choice to free from stress and went to the mall. Basically mall which is building must have fulfiled the security standar which means it has to attend to the function, and or requirements, and/or operation of buildings as stated in Undang-Undang No.28 Tahun 2002 on building. One of the aspect that must be fulfiled is safety for the visitor, the security in the emergency situation such as fire, that’s why building must have good management of fire prevention, one of the elements of fire protection system is an emergency response unit the provisons stipulated in the Peraturan Menteri Pekerjaan Umum No.20 Tahun 2009 on technical guidlines of fire management in urban city. Mall X has been implemented the system of prevention of an emergency situation and the result is good. This is evidenced based on the result of interview with 3 key informant and 1 triangulatin. The results showed that for the emergency response unit is already well underway, the regulation has also been created and run optimally, but there are some things that need to be refined further by Mall X regarding to the recruitment of a Fire Safety Manager to be responsible for the implementation of the emergency management, so that there is no overlap job betwen one and other departements.